Cryoresistance of Silver Carp Sperm after Stimulation by Widely Used Hormonal Preparations - Butskyi, Kyrylo I.; Puhovkin, Anton Yu. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):177.